Ragam Dieksis dalam Dunia Robohnya Surau Kami: Studi Kasus pada Karya A.A. Navis - Wardedy Rosi; Ila Maghfiroh (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Language is a communication tool that connects messages between the speaker and the listener through various pragmatic contexts such as interpersonal relationships, event backgrounds, discussion topics, and communication media. Lexicons in speech often contain numerous references, especially deictic lexicons that rely on context for accurate interpretation. This research employs a qualitative descriptive approach to explore the various styles of deictic language in the short story "Robohnya Surau Kami" by A.A. Navis, avoiding the use of numerical statistics and focusing more on qualitative analysis of the findings. From this analysis, the researcher identifies various types of deixis, such as Personal Deixis, Place Deixis, Time Deixis, Discourse Deixis, Social Deixis, True & Non-True Deixis, and Kinesic & Symbolic Deixis in the work.